Ultrafast lattice response of photoexcited thin films studied by X-ray diffraction - Daniel Schick; Marc Herzog; André Bojahr; Wolfram Leitenberger; Andreas Hertwig; Roman Shayduk; Matias Bargheer (Structural Dynamics, 2014)
Using ultrafast X-ray diffraction, we study the coherent picosecond lattice dynamics of photoexcited thin films in the two limiting cases, where the photoinduced stress profile decays on a length scale larger and smaller than the film thickness. We solve a unifying analytical model of the strain propagation for acoustic impedance-matched opaque films on a semi-infinite transparent substrate, showing that the lattice dynamics essentially depend on two parameters: One for the spatial profile and one for the amplitude of the strain. We illustrate the results by comparison with high-quality ultrafast X-ray diffraction data of SrRuO3 films on SrTiO3 substrates.